Factors affecting the quality of technical processes training - Jaafar, Che Nor Aiza; As'arry, Azizan; Ismail, Rezawati; Zainol, Ismail; T-Dele-Afolabi, Temitope (2021)
Technical Process Training (TPT) and Technical and Vocational Education and Training (TVET) are broadly recognized as a major driving force for the socio-economic development and technological expansion of countries. Manpower Department Technical Institution (MDTI) plays an important role to develop the skill workforce through the design of technical curricula and it can be achieved by continuously improving and sustaining the quality of the programme offered. The purpose of study is to discover and analyse the factors that affect the quality of TPT and TVET system in MDTI. The questionnaire consists of 54 items has been developed to gain the instructors’ opinion on various factors related to the students, instructors, training institution, responsible agency and improvement strategies which accessing the quality of TPT and TVET. The relationship between factors and quality were tested at significance level of 0.05 using Spearman’s rank correlation test. 480 instructors of MDTI fully participated in the study and data exposed that student attitude and implementing the improvement strategies are the main challenges in sustaining the quality of TPT and TVET. Developing and enhancing the partnership between technical institutes and industries were statistically proven to be the most effective improvement strategies. This study also revealed that adequate facilities, provision of latest equipment and tools can strengthen the quality of TPT and TVET in technical institution.